Contribuições do saber tecnológico para o curso de mestrado profissional -MPGOA - Limeira, Jean Carlos Gomes (2023)
The main objective of this research was to analyze how technological knowledge contributes to the PMC training itinerary. To achieve this objective, the following specific objectives were outlined: i) identify technological knowledge in the PMC training; ii) understand student perception regarding the appropriation of technological knowledge in the formation of the PMC; iii) map the products of PMC in administration in Brazil. To this end, it focused on the following constructs: intersections between technology and technological knowledge, learnings versus knowledge, technological knowledge: how to define it?, construction of technological knowledge in light of the epistemology of complexity, technological knowledge: a path for its development?, training itineraries of the Professional Master's Course (PMC). The methodological path involved two qualitative phases. The first phase was responsible for the conception of technological knowledge. The second phase involved the mobilization of technological knowledge, covering objectives one and two. To this end, a semi-structured interview was applied, with the participation of 15 respondents. Which were accessed through the snowball technique. To analyze data from phases one and two, Narrative Analysis (NA) was used, which supported the achievement of objectives one and two. To achieve objective three, a documentary collection was carried out on the Sucupira Platform website, with the support of Content Analysis. From the findings of the first phase, two categories of analysis emerged that were discussed in detail in the analysis chapter, in the same way the second phase saw the emergence of three categories that were also detailed in the analysis chapter. The first phase revealed that technological knowledge is linked notably to technological artifacts and tools, access to technological knowledge occurred through some disciplines, and punctually in their final course work. For some interviewees, they identified almost no connection with technological knowledge. The second phase revealed the importance of technological knowledge in professional performance, as well as the contribution of technological knowledge as a promoter of practical solutions for solving real problems in organizational and social systems. Finally, the data from the documentary collection (objective 3) initially revealed that only two programs deliver their final course work in addition to the dissertation. However, after visiting the repository of theses and dissertations from these institutions, it was realized that the dissertation persists as a final course work. Finally, it was noticed that there is still a lack of practical knowledge within the PMC, and that this absence should be seen as a point of weakness in the PMC's instructional design. It is expected that, among the agents involved in the PMC, a more focused look at the adoption and use of technological knowledge in their training process will be awakened, and that teachers and students will be mainly responsible for this awakening.